NEW RECORDS OF THE PONTELLlD SPECIES (COPEPODA: CALANOIDA) IN INDONESIAN WATERS, WITH NOTES ON ITS SPECIES-GROUPS - MUlyadi Mulyadi (BRIN Publishing (Penerbit BRIN), 2002)
During taxonomic studies on the pelagic copepods of the Indonesian seas, 15 species of Pontellidae were identified for the first time from the area. The species recorded are: Calanopia australica Bayly & Greenwood, 1963, Labidocera bengalensis Krishnaswamy, 1951, L. sinilobata Shen & Lee, 1963, Pontella diagonalis Wilson, 1950, P. forcicula Scott, 1909, P. latifurca Chen & Zhang, 1965, P. spinipes Giesbrecht, 1889, P. tridactyla Shen & Lee, 1963, P. valida Dana, 1849, Pontellopsis herdmani Scott, 1909, P. inflatodigitata Chen & Shen, 1974, P. scotti Sewell, 1932, P. yamadae Mori, 1937, Pontellina morii Fleminger & Hulsemann, 1974, and P. sobrina Fleminger & Hulsemann, 1974. Descriptions, measurements and figures are given for those species, along with a review of their distribution over the world's oceans, and with taxonomic remarks, ecological notes, and restricted synonymies.